Deciding What's True : the Rise of Political Fact-Checking in American Journalism. - Graves, Lucas (Columbia University Press, 2016)
Over the past decade, American outlets such as PolitiFact, FactCheck.org, and the Washington Post's Fact Checker have shaken up the political world by holding public figures accountable for what they say. Cited across social and national news media, these verdicts can rattle a political campaign and send the White House press corps scrambling. Yet fact-checking is a fraught kind of journalism, one that challenges reporters' traditional roles as objective observers and places them at the center of white-hot, real-time debates. As these journalists are the first to admit, in a hyperpartisan worl.